THE EFFECT OF PARITY, AGE, BODY MASS INDEX ON THE INCIDENCE OF THE PREECLAMSIA STUDY IN Dr. HIKMAH - Zuryati M.Kes (NHM PRESS, 1970)
Preeclampsiais a disease with high morbidity and mortality. Preeclampsia is the main cause of maternal death after bleeding.The Problem in this study was that there are still many pregnant woment with preeclamsia ( 16,6 % ).The purpose of this study is to analyze the effect of Parity, Age, Body Mass Index (BMI) on the incidence of preeclampsia. The design of this study was Analytical with a Retrospective Case Study approach using secondary data. Independent variable were Parity, Age, BMI. The dependent variable was the incidence of preeclamsia. The population of this study were 2120 pregnant women and 337 pregnant women were taken in Syamrabu general HospitalBangkalan. The sampling technique used Simple Random Sampling. While the data collection tool used Medical Records with Wilks' Lambda test statistics.After the test, the research was worth researching. The results showed that the majority of pregnant women parity were 209 pregnant women (62.0%), the majority of pregnant women aged> 20 years - <35 years (no risk) as many as 212 pregnant women (62.9%), maternal BMI pregnant Almost half of them were 30- 39.9 as many as 129 pregnant women (38.3%), and the majority of them did not have as many as 227 preeclampsia pregnant women (67.4%).There was no significant relationship (meaning) between parity and occurrenced of Preekslamsi with P Value (0.334) >α = 0.05 so that H0 was accepted and H1 was rejected.There was a significant (mean) relationship between age factor with Preekslamsi with P Value (0.000) <α= 0.05 so that H0 wasrejected and H1 wasaccepted.And there was a significant (mean) relationship between the body mass index (BMI) with the occurrence of Preekslamsi with P Value (0.000) <α = 0.05 so that H0 was rejected and H1 was accepted. The results of the study showed that Pre-eclampsia was affected by Parity, Age and BMI so the researchers hope thatpregnant women doAntenatal Care regularly,rest and diets high in protein and low in lems, carbohydrates, salt.